Using of Hyperbranched Poly(amidoamine) as Pretanning Agent for Leather - Amal Amin Ibrahim; Moshera S. A. Youssef; El-Shahat H. A. Nashy; Mohamed M. Eissa (International Journal of Polymer Science)
Although chrome is considered as the major tanning agent in the production of all types of hides and leather worldwide, it represents a serious source of environmental pollution. Therefore, polyamidoamine hyperbranched polymer (HPAM) was involved in pretanning of the depickled hides to enhance the chromium uptake during the tanning process. The key parameters which affect the exhaustion and fixation of chrome tan including shrinkage temperature of the tanned leather were studied. The results showed a significant improvement in the chrome exhaustion, the shrinkage temperature, and the texture and softness of the leather treated by HPAM.